1976
DOI: 10.1128/aac.10.2.370
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility of Pathogenic Naegleria and Acanthamoeba Species to a Variety of Therapeutic Agents

Abstract: Six pathogenic strains ofNaegleria fowleri, two ofAcanthamoeba castellanii, and three ofAcanthamoeba polyphaga were tested in vitro for susceptibility to a variety of potentially useful therapeutic agents. Minimal motility inhibitory concentrations and minimal inhibitory concentrations were determined by a technique of subculturing pure clones of amoebae in plastic tissue culture chamber slides containing liquid axenic media and serially diluted drug, incubating at 3000 forAcanthamoeba and at 3700 forNaegleria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
30
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…There was no indication ofsynergy when AMB was combined with miconazole or when the methyl ester of AMB was combined with either minocycline, tetracycline, or miconazole. DISCUSSION AMB (5,8,9,17), tetracycline (19), rifampin (19), clotrimazole (9,12), and miconazole (9,21) have all shown activity against Naegleria spp. The majority of the assays of these reagents have been carried out either on agar plates or in axenic media, both with and without bacteria as an added nutrient.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…There was no indication ofsynergy when AMB was combined with miconazole or when the methyl ester of AMB was combined with either minocycline, tetracycline, or miconazole. DISCUSSION AMB (5,8,9,17), tetracycline (19), rifampin (19), clotrimazole (9,12), and miconazole (9,21) have all shown activity against Naegleria spp. The majority of the assays of these reagents have been carried out either on agar plates or in axenic media, both with and without bacteria as an added nutrient.…”
Section: Resultsmentioning
confidence: 98%
“…Antiamoebic effects of drugs that have been previously noted include inhibition of growth (5,8,9), inhibition of amoebic motility (5,8,9), and cytotoxic changes observed by light or electron microscopy (17). Definitions of the MIC of a drug have varied in previous studies (5,8,9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since primary amebic meningoencephalitis was identified, a wide range of therapeutic agents against N. fowleri have been evaluated, including many antifungal, antiprotozoal, antibacterial, and antipsychotic agents. Most of these drugs were determined to have little or no efficacy against N. fowleri, either in vitro or in vivo (5)(6)(7)(8)22).Of the drugs that have been evaluated against N. fowleri, amphotericin B, an antifungal drug, is the only agent with established clinical efficacy. Studies have demonstrated the in vitro and in vivo activity of amphotericin B against various strains of N. fowleri (5-8, 13, 17, 19, 20, 21), and at least seven patients with primary amebic meningoencephalitis have been successfully treated with amphotericin B alone or in combination with other drugs (1,2,14,16,19,25).…”
mentioning
confidence: 99%